Faktor-Faktor Penentu Keputusan Investasi Pada Generasi Milenial Dan Gen Z - Dina Evita Junianti; Tenriwaru, Tenriwaru; Andi Nirwana Nur (LPPM UBP, 2025)
This study aims to analyze the factors that influence investment decisions among Millennials and Gen Z in Makassar City. The sample of this study consisted of 100 respondents selected using purposive sampling techniques. The research method used a survey approach with multiple linear regression analysis to test the hypothesis. The results of the study indicate that financial literacy has a positive but insignificant effect on investment decisions. Investment motivation is proven to have a significant positive effect on investment decisions. Financial behavior also has a positive and significant effect on investment decisions. Overall, these three variables simultaneously have a positive and significant effect on investment decisions. The implications of this study indicate that increasing motivation and good financial behavior can encourage wiser investment decision-making among Millennials and Gen Z.